A Methodological Approach for Researching National Classroom Practices - Meng, Yew Tee; Samuel, Moses; Norjoharuddeen, Mohd Nor; Shanthi, Nadarajan (Centre for Research in International and Comparative Education (CRICE), 2016)
Little continues to be known about what actually happens in classrooms, particularly from a national perspective. Descriptions of classroom practices from a national vantage point can provide a bird’s eye view of salient patterns and variations within an education system, especially one as centralised as that of Malaysia. With these descriptions, especially if the primary data consists of video recordings, one can also begin to compare movements in classroom practices across time and space; theorise about the nature of practice within the system as well as inform policy deliberations. This paper examines key methodological decisions of conducting a national study to research classroom educational practice within Malaysia’s public school system. The case is made for the use of such studies to gain a bird’s eye perspective of classroom practices in a national system as well as to lay the foundations for inter-system comparisons. Potential implications and opportunities of these types of studies are also discussed.